The Genesis of the Modern Academic Library in China: Western Influences and the Chinese Response. - Jing Liao (Libraries & Culture)
From early antiquity through the end of the nineteenth century, the primary missions of Chinese imperial and private libraries were to collect and preserve books and documents. Except for a few isolated historical periods, these libraries rendered no service to the public. The Metropolitan University Library in Beijing, founded in 1898, was China's first modern academic library with a clear goal of serving a burgeoning program of public higher education. The tale of the founding of this library reveals an intriguing story of tension between the modern Western and traditional Chinese concepts of what a library should be. This article examines the changing patterns of Western influences and Chinese responses in the sociopolitical and cultural arenas in the nineteenth century and considers how, amidst this intense Western and Chinese engagement and confrontation, the debate on library reform emerged and eventually led to the birth of the modern Chinese academic library.